ANALYSIS OF DUST GASES SYSTEMS OF DIFFERENT GENRES FROM LOCAL INDUSTRIES AND CONDUCT OF THEIR CLEANING EXPERIMENTS - A.A. Muydinov; A.O. Khoshimov (European Science Publishing, 2023)
Separation of various particles from the air and technological and sanitary treatment of industrial waste gases is one of the widely used processes in the production of chemical and food products. It is an urgent task to implement these processes and to rationally select the mode of the process for the production of a competitive and high-quality product, as well as to develop equipment of a new construction with high efficiency. In this regard, there is a tendency to use devices working in the wet method. The complexity of the phase interaction and hydrodynamic structure in the wet cleaning of industrial dust gases, a wide range of changes in the physico-chemical properties of dust, and the interdependence of structural and mode parameters make the process unique represents.
Keywords: filters, NIIO Gas, mass, aerodynamic, dust content, hydraulic resistance, fraction, U-shaped micro manometer.